2021
DOI: 10.1186/s13045-021-01155-6
|View full text |Cite
|
Sign up to set email alerts
|

Combine and conquer: manganese synergizing anti-TGF-β/PD-L1 bispecific antibody YM101 to overcome immunotherapy resistance in non-inflamed cancers

Abstract: Background Our previous work showed that the anti-TGF-β/PD-L1 bispecific antibody YM101 effectively overcame anti-PD-L1 resistance in immune-excluded tumor models. However, in immune-desert models, the efficacy of YM101 was limited. Bivalent manganese (Mn2+) is identified as a natural stimulator of interferon genes (STING) agonist, which might enhance cancer antigen presentation and improve the therapeutic effect of YM101. Methods The effect of Mn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 66 publications
2
46
0
Order By: Relevance
“…Our results further demonstrated that high PYGL expression was closely associated with infiltration of immune cells in tumors, with this expression pattern also positively correlated with cancer associated fibroblasts (CAFs). Previous studies have shown that CAFs inhibit T cell infiltration by secreting peritumoral collagen and TGF-Beta/PD-L1 specific antibody YM101, while M7824 could effectively suppress CAFs activity thereby promoting T cell infiltration ( Lan et al, 2018 ; Yi et al, 2021a ; Yi et al, 2021b ). Additional research evidences have shown that the extracellular matrix produced by CAFs can also limit efficacy of tumor therapy ( Ziani et al, 2018 ; Dou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results further demonstrated that high PYGL expression was closely associated with infiltration of immune cells in tumors, with this expression pattern also positively correlated with cancer associated fibroblasts (CAFs). Previous studies have shown that CAFs inhibit T cell infiltration by secreting peritumoral collagen and TGF-Beta/PD-L1 specific antibody YM101, while M7824 could effectively suppress CAFs activity thereby promoting T cell infiltration ( Lan et al, 2018 ; Yi et al, 2021a ; Yi et al, 2021b ). Additional research evidences have shown that the extracellular matrix produced by CAFs can also limit efficacy of tumor therapy ( Ziani et al, 2018 ; Dou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are multiple rationally designed dual-targeted immune checkpoint bispecific molecules aiming to provide superior activity. Clinical trials are testing a number of immune checkpoint bispecific antibodies, including PD-1xCTLA-4, PD-1xLAG3 (lymphocyte activation gene-3) and PD-L1xTGFb [ 112 114 ].…”
Section: Targeting Antigensmentioning
confidence: 99%
“…Therefore, blocking TGF-beta significantly enhanced the efficacy of anti-PD-1/PD-L1. Recently, bispecific antibodies targeting TGF-Beta and PD-L1 exhibited superior antitumor activity (38)(39)(40), indicating that the combination of these drugs with ICIs, as well as antibodies targeting TGF-Beta may have better therapeutic effects for patients.…”
Section: Discussionmentioning
confidence: 99%